Clustering Activities of Subjects of the Cotton Textile Industry - Khalikov Tolibjon Luptullaevich (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The article discusses the theoretical issues and principles of the formation of agro-clusters, as well as the development trends of this system in the cotton-textile industry of the Republic of Uzbekistan, its features and advantages. The effective use and existence of business clusters are considered within the framework of such aspects as structural, functional, purposeful, evolutionary on the platform of categorical-system methodology.